Vertebrobasilar Dolichoectasia as A Rare Cause of Trigeminal Neuralgia - A Case Report - Kabir, Md. Suman; Ashish Chowdhury,; Subash Kanti Dey,; Md. Abdullah Al Muzahid,; Sujan Saha,; Uttam Roy,; Md. Moniruzzaman Bhuiyan,; Md. Rafiqul Islam, (Bangladesh Journal of Neuroscience, 2026)
We present a case of 24 years old young male with trigeminal neuralgia due to vertebrobasilar dolichoectasia, a rare condition characterized by enlargement, tortuosity, or elongation of intracranial arteries. Dolichoectatic vessels can cause dysfunction of cranial nerves through direct vascular compression. Vertebrobasilar dolichoectasia is a rare cause of trigeminal neuralgia and a successful outcome can be achieved with microvascular decompression. The relationships of vertebrobasilar dolichoectasia with the particularities of neurovascular conflict and images findings are discussed.